Islamic activists : the anti-enlightenment democrats - Abdelkader, Dina (Pluto Press, 2011)
In the hysteria surrounding political Islam, it is difficult to find analysis that doesn't feel the need to justify the existence of Islamic leaders or react to the West's fear of 'extremists'. In this book, the author shows us what Islamic leaders and activists believe and what they think about just governance.